Business Development Strategy Using SWOT Analysis at Pentol Boska in Sidoarjo Regency - Nanda Nur Humairoh Arifin; Jojok Dwiridotjahjono (Universitas KH. Abdul Chalim Mojokerto, 2024)
Strategy can encourage companies to consider the future to shape it proactively, so it is very important to see market opportunities in a business to grow. The purpose of this study was to determine the business development strategy using SWOT analysis on Pentol Boska in Sidoarjo Regency. The method used in this research is descriptive research with a qualitative approach. Sources of data were taken in this study through interviews, observation, and documentation. From this study, it resulted in the SWOT analysis quadrant in the IFAS matrix resulted in a higher strength score value (strength) than a lower weakness score value. Meanwhile, the EFAS matrix produces a higher score value of opportunities (opportunities) than a lower score value of threats (threats), so the SWOT diagram is in quadrant 1 with a score of 1.64 > 0.71. This situation is a favorable opportunity for the Pentol Boska business, where the strategy used supports an aggressive strategy for various opportunities and strengths that have been identified.